Learners’ View of English Language Learning Through Modular Approach - A Phenomenology (American Journal of Interdisciplinary Research and Innovation, 2023)
This research aimed to explore the views of English language learners of selected Grade six of Tenorio Elementary School, Maguindanao-II Division, who were undergone the modular approach to learning during the COVID-19 Pandemic. The Collaizi’s (1978) seven steps strategy in phenomenological approach was utilized to provide rigorous analysis of data. The purposive sampling technique was used to select the participants relevant to the research study. The researchers’ made semi-structure guided interview questionnaire with in-depth interview to the participants to explicate the research phenomena. Thus, study revealed that, learners experiences of modular learning affected by personal, teacher, subject matter and technological factor were Acclimatization to Modular Learning, Extrinsic Motivation, Health Issue, Lack of Adult’s Guidance or Teacher Supervision, Complexity of Subject Matter, and Quality Content of Module. Consequently, learners experiences as affected by technological factors were Power Outrage, Accessible to Internet, Lack of Mobile Phone. Moreover, learners observed attitude among in ELL through modular approach were, Knowledge of Content of Module, Development of Macro Skills, Views of Importance of ELL, Preference of Face to Face Learning. Constant Reading and Pre-reading, and Utilization of YouTube Video Lessons. Hence, the effects of learner’s attitude towards modular approach were, Learning Through Social Media Platform, Lack of Engagement of Learning and Guessing Only of Answers. Therefore, various studies have examined the effects of attitudes on ELL; however, few have worked on the influence of attitudes on ELL in the course of the Covid-19 pandemic. Synonymous to popular belief that a proper and positive attitude is imperative for achievement in language learning (Gardner, 1985), the study finds out that positive attitude towards modular learning brings positive actions which resulted to positive effects in ELL performance and that a negative attitude brings unlikely effect in ELL performance.